2016
DOI: 10.1016/j.bjid.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Improving hand hygiene compliance among healthcare workers: an intervention study in a Hospital in Guizhou Province, China

Abstract: This study demonstrates that a significant improvement in compliance with HH can be achieved through a systemic, multidimensional intervention approach involving all categories of healthcare workers in a hospital setting, which may result in a decrease of the HAI rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
4
28
3
Order By: Relevance
“…Findings in this study show that adherence rate to hand hygiene was poor (26.6%), which conformed with reported adherence rates of 20% to 40% (Sakihama et al, ); Scheithauer et al, ). However, adherence to hand hygiene in our study was less than other Chinese studies, with adherence rates reported as 52% to 80% (Mu et al, ; Su et al, ). The most likely cause for these results is that the observations in other studies were primarily conducted for short sessions.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Findings in this study show that adherence rate to hand hygiene was poor (26.6%), which conformed with reported adherence rates of 20% to 40% (Sakihama et al, ); Scheithauer et al, ). However, adherence to hand hygiene in our study was less than other Chinese studies, with adherence rates reported as 52% to 80% (Mu et al, ; Su et al, ). The most likely cause for these results is that the observations in other studies were primarily conducted for short sessions.…”
Section: Discussioncontrasting
confidence: 83%
“…However, adherence to hand hygiene in our study was less than other Chinese studies, with adherence rates reported as 52% to 80% (Mu et al, 2016;Su et al, 2015). The most likely cause for these results is that the observations in other studies were primarily conducted for short sessions.…”
Section: Relationship Between Nursing Workloads and Adherence To Hacontrasting
confidence: 82%
“…The same trend was observed in most departments. Similar results were shown through literature around the world [1,10,12,13,15,17,[29][30][31][32][33] reflecting the ability of multimodal interventions to raise awareness about the HH importance. However, it was not always the case.…”
Section: Discussionsupporting
confidence: 84%
“…In the second phase, an educational campaign armed with data from direct observations of hand hygiene compliance was implemented, targeting multidisciplinary healthcare workers. Hand hygiene compliance improved from 38% to 76% in response to the campaign coupled with a significant increase in product usage over the same time period (Mu et al, 2016).…”
Section: Direct Observation Hand Hygiene Monitoringmentioning
confidence: 97%
“…Ongoing education combined with feedback of hand hygiene compliance data was also successful in a 17-month study conducted in China by Mu et al (2016). In the first phase of the study, increased availability of hand hygiene dispensers and supplies was engineered into the clinical environment.…”
Section: Direct Observation Hand Hygiene Monitoringmentioning
confidence: 99%